2014
DOI: 10.1109/tnsre.2014.2308997
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Transcranial Direct Current Stimulation With a Detailed Anisotropic Human Head Model

Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique able to induce long-lasting changes in cortical excitability that can benefit cognitive functioning and clinical treatment. In order to both better understand the mechanisms behind tDCS and possibly improve the technique, finite element models are used to simulate tDCS of the human brain. With the detailed anisotropic head model presented in this study, we provide accurate predictions of tDCS in the human brain for six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(195 citation statements)
references
References 61 publications
7
181
6
1
Order By: Relevance
“…Relevant parameters include electrode size and placement, along with stimulation duration and intensity [12,51,52]. It is also unclear as to the spatial extent of the stimulation, although Rampersad [53] found largely focal effects when using the same configuration employed within this study. However, this is difficult to measure without sophisticated methods and is likely to vary across individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Relevant parameters include electrode size and placement, along with stimulation duration and intensity [12,51,52]. It is also unclear as to the spatial extent of the stimulation, although Rampersad [53] found largely focal effects when using the same configuration employed within this study. However, this is difficult to measure without sophisticated methods and is likely to vary across individuals.…”
Section: Discussionmentioning
confidence: 96%
“…A recent review of 61 studies applying tDCS to the DLPFC found a lack of consistency in outcomes making causal conclusions between DLFPC stimulation and a particular cognitive function difficult (Tremblay et al, 2014). One reason for the inconsistency is that tDCS appears to simultaneously modulate activity in a number of brain areas subserving a variety of cognitive functions with the maximum field strength being located some distance (20-40 mm) from the target area (e.g., DLPFC) (Rampersad et al, 2014).…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
“…Indeed, caution must be exercised because we cannot assume that the area receiving maximum stimulation is directly beneath the electrode, as the level of current delivered to different areas can vary substantially (Rampersad et al, 2014). Small drifts in the position of electrodes that can occur during a 20 min tDCS session can also significantly change the intensity and distribution of the current delivered to the brain (Woods et al, 2015).…”
Section: Lack Of Focal Stimulationmentioning
confidence: 99%
“…Furthermore, epidural anodal DCS of the cerebellum of rodents induces reorganisation of M1, reducing its excitability along with that of the motoneurons in the anterior horn of the spinal cord [53]. Investigations aimed at modelling the DCS electric field in humans demonstrated that maximal activation was localised to the targeted cerebellar hemisphere [54]. In contrast, repetitive TMS protocols in Parkinson's disease patients were found to alter metabolic activity in both cerebellar cortex and the deep cerebellar nuclei [55].…”
Section: Non-invasive Cerebellar Stimulationmentioning
confidence: 99%